Diabetes mellitus tipo 2 como factor de riesgo para cáncer de mama en mujeres adultas - Murga Quezada, Darwin Smith (2016)
Breast cancer (BC) is the leading neoplastic malignancy among females worldwide, while Type 2 Diabetes Mellitus (DM type 2) is a prevalent and growing problem of health in our country, so there is controversy on the risk involved have DM type 2 to development breast cancer. PROBLEM: Is type 2 Diabetes Mellitus a risk factor to Breast Cancer in adult women? OBJECTIVES: To determine whether type 2 Diabetes Mellitus is a risk factor in Breast Cancer Patients adult women. MATERIAL AND METHOD: Study Design: Analytical-cases and controls. The medical records were obtained from the statistical file Bethlehem Hospital of Trujillo (HBT) from 2004 to 2013. The sample consisted of 27 cases and 54 controls, in the control group, the selection of medical record was random. Information was collected from both groups using a datasheet. Statistical analysis was applied Chi - square test with significance level < 0.05, to assess associations between each risk factor and BC risk with adjusted odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS: Of the total sample (81 patients): 27 (33.3%) had presented diagnosis of Breast Cancer white 54 (66.6%) had not presented. The average age in the case group (57.8 years) was higher than in the control group (57.1 years) without statistical significance (p = 0.75). The 88.6 % of patients with Breast Cancer were between 40 and 70 years old. 70.4% of control patients were overweight (BMI 25- 29.9 kg / m2). The odds ratio (OR) for breast cancer in women with DM type 2 was 2.1 (95% confidence interval (CI), 1.1-7.0) that allows us to establish an increased risk for the association between Breast Cancer and type 2 Diabetes Mellitus; also to find the p-value = 0.045, it indicate that the association is statistically significant. CONCLUSIONS: Type 2 Diabetes Mellitus is a factor significantly associated with increased BC risk among adult women treated at the Bethlehem Hospital of Trujillo